Treatment of immunoglobulin: a nephropathy - Schiele, Jörg; Nowack, Rainer; Julian, Bruce A.; Woude, Fokko J. van der (Annales de médecine interne, 1999)
In this review, therapeutic trials for treatment of IgA nephropathy (Berger's disease) are reviewed and discussed. No diseasespecific therapy exists. For treatment of hypertensive patients, angiotensin converting enzyme (ACE) inhibitors are preferred. They also decrease proteinuria and probably slow disease progression. However, there are still no controlled data on the effectiveness of ACEinhibitors in the absence of hypertension or proteinuria. Renewed enthusiasm for treatment with fish oil arose after the publication of a randomized controlled trial in 1994 and longterm followup data of the trial cohort in 1998. Corticoid therapy in IgA nephropathy has been advocated for patients with nephrotic syndrome or crescentic disease. A recent nonrandomised trial with longterm followup suggests that, in the presence of moderate proteinuria, corticosteroids may ameliorate renal function if administered before the creatinine clearance has decreased below 70 ml/min. Preliminary data suggest that mycophenolate mofetil (MMF) may reduce the risk of clinically significant IgA nephropathy recurring in kidney allografts. Many other promising treatment approaches have been tested, but in most instances results are insufficient for unequivocal conclusions. Several randomized controlled clinical trials are currently testing prednisone, fish oil, ACEinhibitors, cyclophosphamide, MMF and vitamin E. In the absence of a diseasespecific treatment, control of hypertension, proteinuria and probably dyslipidemia are pivotal. Chronic or recurrent infection including tonsillitis should be treated effectively. Control of daily protein intake to 0,70,8 g/kg body weight may retard disease progression.
Gesehen am 29.09.2022